Chapter Per l'edizione del Corbaccio: preliminari allo studio della tradizione - Giglio, Lorenzo (Studi e saggi, 2022)
The paper examines some critical aspects of the manuscript tradition of Boccaccio's Corbaccio, starting from the results of the very few studies on the subject. Besides proposing an updated list of all the 79 available manuscripts that hand down the work, whose yet we don't have any critical edition, he then demonstrates, through a number of examples, the benefits of widening perspective to the codes of the non-α family, but also of a comprehensive reconsideration of the status of α itself. In the absence of a solid classification of the whole manuscript tradition, the "traditional" hypothesis that the α2 group (and in particular the Mannelli codex) represents an advanced redaction of Boccaccio's «umile trattato» risks to be too conditioning if assumed at such a preliminary stage.